2022
DOI: 10.7150/jca.76945
|View full text |Cite
|
Sign up to set email alerts
|

HOXC10 Promotes Metastasis in Colorectal Cancer by Recruiting Myeloid-derived Suppressor Cells

Abstract: Background: Since metastasis is the primary cause of death in human colorectal cancer (CRC) patients, the exact mechanism underlying CRC metastasis remains unclear. Here, we provide evidence for a unique function of HomeoboxC10 (HOXC10) in driving CRC metastasis, as well as treatment options for these subpopulation patients. Methods: Immunohistochemistry detected the expression of HOXC10 in the human CRC cohort. The function of HOXC10 in CRC metastasis was investigated using the cecum orthotopic model. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Both myeloid-derived suppressor cells (MDSCs) and tumour-associated macrophages (TAMs) can be recruited by F. nucleatum to suppress immunity in CRC patients [ 61 ]. Among them, MDSCs have become an important component of TME, which can significantly inhibit T cell activity, with potent immunosuppressive effects and the potential to promote CRC metastasis [ 62 , 63 ]. Additionally, macrophages have the ability to phagocytose tumour cells alive, leading to the death of tumour cells, which seems to be an important mechanism of tumour immunity [ 64 ].…”
Section: Mechanisms Underlying the Promotion Of Crc Metastasis By Imb...mentioning
confidence: 99%
“…Both myeloid-derived suppressor cells (MDSCs) and tumour-associated macrophages (TAMs) can be recruited by F. nucleatum to suppress immunity in CRC patients [ 61 ]. Among them, MDSCs have become an important component of TME, which can significantly inhibit T cell activity, with potent immunosuppressive effects and the potential to promote CRC metastasis [ 62 , 63 ]. Additionally, macrophages have the ability to phagocytose tumour cells alive, leading to the death of tumour cells, which seems to be an important mechanism of tumour immunity [ 64 ].…”
Section: Mechanisms Underlying the Promotion Of Crc Metastasis By Imb...mentioning
confidence: 99%
“…In CRC and pancreatic cancer, MDSCs play an important role in enabling this process. PMN-MDSC depletion inhibits progression of CRC peritoneal disease [ 13 ], while CXCR2 inhibitor can reduce the rate of metastasis by reducing the MDSC infiltration [ 14 , 15 ]. Finally, CXCR2+ MDSCs in the premetastatic niche promote CRC tumor cell survival [ 16 ], and M-MDSCs promote the growth of CRC micro-metastases to macro-metastases [ 17 ].…”
Section: Mdscs Drive Metastasis In Gi Malignanciesmentioning
confidence: 99%
“…Combining different immunotherapeutic agents, such as immune checkpoint inhibitors, adoptive T cell therapies, cytokines, and vaccines, can create a more comprehensive and dynamic immune response against the disease. For example, studies indicated that when used as a single agent, IDO-1 or CXCR-2 inhibitors exerted little antitumor efficacy, while combination with other therapies showed markedly enhanced antitumor effectiveness [ 32 , 33 , 34 , 35 ]. On the contrary, a phase 1 clinical study yielded inconclusive evidence concerning the potential benefits of combined therapy incorporating the IDO-1 inhibitor (navoximod) and the PD-L1 inhibitor (atezolizumab) in solid tumors, including CC [ 36 ].…”
Section: Introductionmentioning
confidence: 99%